Cattle and its mythical-epic themes in Shahnameh, Garshasbnameh, Koushnameh, Borznameh, Bahmannameh and Banogoshasbnameh - Sharifzad, Nasrin (2021)
In Shahnameh and other epic poems, which reflect the myths, the life of primitive and ancient Iranian societies, animals and other animals are of great importance and go beyond their normal features and status. Myths that are truths of the thoughts and ideas of the first people, which are mixed with different stories and are expressed symbolically and cryptically. Epic events are usually the result of linking these myths to history. Among the animals, "cow" is one of the actors that is mentioned in Ferdowsi's Shahnameh and other epic poems, and has its own themes and themes. This article aims to examine the place of the cow in the myths and civilization of the past, as well as in the most valuable epic work, Shahnameh and five other epic poems (Garshasbnameh, Kushnameh, Bahmannameh, Banogshsabnameh and Borzoonameh) and the most important mythological themes. Extract, classify and analyze the epic and ritual of this animal. These themes are: lexical and symbolic meaning of cow, the place of cow in myths and ancient Iran, the relationship between creation and death of Kiomars with cow, cow relationship with human psyche and moon , Heroic Cow, Heroic Breeding, Sculpture or Composition, Gausser Stick,, Cow, Name of the Tower in the Sky, Cattle Totem.